Conductive laminate and method for manufacturing conductive laminate

JP7636427B2Active Publication Date: 2025-02-26FUJIFILM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022553999
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-30
Filing Date
2021-09-28
Publication Date
2025-02-26
Estimated Expiration
2041-09-28

AI Technical Summary

Benefits of technology

【0007】 本開示によれば、体積抵抗率が低く、かつ、放熱性に優れる導電積層体、及び、導電積層体の製造方法が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636427000001
    Figure 0007636427000001
  • Figure 0007636427000002
    Figure 0007636427000002
  • Figure 0007636427000003
    Figure 0007636427000003
Patent Text Reader

Abstract

This conductive laminate is provided with a substrate and a conductive ink film provided on the substrate. Defining the surface of the conductive ink film near the substrate as the first principal surface and the surface far from the substrate as the second principal surface, the first porosity of the region from the 50% thickness position to the second principal surface in the direction from the first principal surface towards the second principal surface is 15%-50%, and the second porosity of the region up to the 10% thickness position in the direction from the first principal surface towards the second principal surface is lower than the first porosity. A manufacturing method for the conductive laminate is also provided.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a conductive laminate and a method for manufacturing a conductive laminate. [Background technology]

[0002] 2. Description of the Related Art Conductive laminates in which a conductive film is provided on a substrate are used as electronic materials for producing various electronic devices.

[0003] For example, JP 2010-183082 A describes a substrate including a base material and a conductive pattern provided on the base material, the conductive pattern including conductive inorganic metal particles and an organometallic complex that provides conductive channels between at least some of the conductive inorganic metal particles. Summary of the Invention [Problem to be solved by the invention]

[0004] In some cases, a conductive laminate is required to have both low volume resistivity and heat dissipation properties.

[0005] The present disclosure has been made in consideration of the above circumstances, and according to one embodiment of the present invention, a conductive laminate having low volume resistivity and excellent heat dissipation properties, and a method for manufacturing the conductive laminate are provided. [Means for solving the problem]

[0006] The present disclosure includes the following aspects. <1> A conductive laminate comprising a substrate and a conductive ink film provided on the substrate, wherein when the surface of the conductive ink film closer to the substrate is defined as a first main surface and the surface of the conductive ink film farther from the substrate is defined as a second main surface, a first porosity in a region from a 50% thickness position from the first main surface toward the second main surface to the second main surface is 15% to 50%, and a second porosity in a region from the first main surface toward the second main surface to a 10% thickness position is smaller than the first porosity. <2> The first porosity is 30% to 40%; <1> The conductive laminate according to claim 1. <3> The second porosity is 20% or less. <1> or <2> The conductive laminate according to claim 1. <4> The conductive ink film contains at least one selected from the group consisting of silver, gold, platinum, nickel, palladium, and copper. <1> ~ <3> 13. The conductive laminate according to claim 12, <5> The conductive ink film has a thickness of 0.5 μm to 30 μm. <1> ~ <4> 13. The conductive laminate according to claim 12, <6> The method includes the steps of: applying a first conductive ink containing a metal salt or a metal complex onto a substrate; baking the first conductive ink; applying a second conductive ink containing metal particles onto the baked first conductive ink; and baking the second conductive ink. <1> ~ <6> 13. A method for producing a conductive laminate according to claim 12. <7> The metal particles are particles containing at least one selected from the group consisting of silver, gold, platinum, nickel, palladium and copper. <7> 2. A method for producing the conductive laminate according to claim 1 . <8> The metal particles have an average particle size of 10 nm to 200 nm. <6> or <7> 2. A method for producing the conductive laminate according to claim 1 . <9> The content of the metal particles is 10% by mass to 90% by mass based on the total amount of the first conductive ink. <6> ~ <8> 13. A method for producing a conductive laminate according to claim 12. <10> The metal salt and the metal complex each contain at least one selected from the group consisting of silver, gold, platinum, nickel, palladium, and copper; <6> ~ <9> 13. A method for producing a conductive laminate according to claim 12. <11> The metal complex is a metal complex having a structure derived from at least one selected from the group consisting of an ammonium carbamate-based compound, an ammonium carbonate-based compound, an alkylamine, and a carboxylic acid having 8 to 20 carbon atoms, and the metal salt is a metal carboxylate having 8 to 20 carbon atoms. <6> ~ <10> 13. A method for producing a conductive laminate according to claim 12. <12> The content of the metal salt and the content of the metal complex are each 10% by mass to 90% by mass relative to the total amount of the second conductive ink. <6> ~ <11> 13. A method for producing a conductive laminate according to claim 12. <13> In the step of applying the first conductive ink, the first conductive ink is applied using an inkjet recording method, and in the step of applying the second conductive ink, the second conductive ink is applied using an inkjet recording method. <6> ~ <12> 13. A method for producing a conductive laminate according to claim 12. <14> In the step of applying the first conductive ink, the temperature of the substrate when the first conductive ink is applied is 20°C to 120°C. <6> ~ <13> 13. A method for producing a conductive laminate according to claim 12. <15> In the step of baking the first conductive ink, the baking temperature is 250° C. or less, and the baking time is 1 minute to 120 minutes. <6> ~ <14> 13. A method for producing a conductive laminate according to claim 12. <16> In the step of applying the second conductive ink, the temperature of the substrate when the second conductive ink is applied is 20°C to 120°C. <6> ~ <15> 13. A method for producing a conductive laminate according to claim 12. <17> In the step of baking the second conductive ink, the baking temperature is 250° C. or less, and the baking time is 1 minute to 120 minutes. <6> ~ <16> 13. A method for producing a conductive laminate according to claim 12. <18> The time from the end of the step of applying the first conductive ink to the start of the step of baking the first conductive ink is 60 seconds or less. <6> ~ <17> 13. A method for producing a conductive laminate according to claim 12. Effect of the Invention

[0007] According to the present disclosure, there are provided a conductive laminate having low volume resistivity and excellent heat dissipation properties, and a method for manufacturing the conductive laminate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The conductive laminate and the method for producing the conductive laminate according to the present disclosure will be described in detail below.

[0009] In this specification, a numerical range indicated using "to" means a range that includes the numerical values ​​before and after "to" as the minimum and maximum values, respectively. In the numerical ranges described in this specification, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in a certain numerical range. In addition, in the numerical ranges described in this specification, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples.

[0010] In this specification, the amount of each component in a composition means the total amount of the multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified. As used herein, a combination of two or more preferred embodiments is a more preferred embodiment. In this specification, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes, as long as the intended purpose of the process is achieved.

[0011] In this specification, the term "image" refers to a film in general, and the term "image recording" refers to the formation of an image (i.e., a film). The concept of "image" in this specification also includes a solid image.

[0012] [Conductive laminate] In the conductive laminate of the present disclosure, when the surface of the conductive ink film closer to the substrate is the first main surface and the surface farther from the substrate is the second main surface, the first porosity in the region from a 50% thickness position from the first main surface toward the second main surface to the second main surface is 15% to 50%, and the second porosity in the region from the first main surface toward the second main surface to a 10% thickness position is smaller than the first porosity.

[0013] The inventors focused on the porosity in a specific region of the conductive ink film and found that when the first porosity is 15% to 50% and the second porosity is smaller than the first porosity, it is possible to achieve both low volume resistivity and high heat dissipation properties.

[0014] In the conductive laminate of the present disclosure, the first porosity of the conductive ink film is 15% or more, so that the heat dissipation properties are excellent, and in the conductive laminate of the present disclosure, the first porosity of the conductive ink film is 50% or less, so that the volume resistivity is reduced.

[0015] Furthermore, in the conductive laminate of the present disclosure, the second porosity of the conductive ink film is smaller than the first porosity, and therefore the volume resistivity is reduced.

[0016] On the other hand, Patent Document 1 does not focus on the porosity of the conductive ink film. In addition, when a conductive laminate is produced by the method disclosed in Patent Document 1, the porosity becomes almost constant throughout the entire conductive ink film, and it is not possible to expect both low volume resistivity and high heat dissipation properties.

[0017] <Base material> The conductive laminate of the present disclosure includes a substrate.

[0018] The material of the substrate is not particularly limited and can be selected according to the purpose. Specifically, the substrate material includes polyimide, polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polycarbonate, polyurethane, polyethylene, polypropylene, polyvinyl chloride, polystyrene, polyvinyl acetate, acrylic resin, AS resin (acrylonitrile styrene resin), ABS resin (acrylonitrile-butadiene-styrene copolymer), triacetyl cellulose, polyamide, polyacetal, polyphenylene sulfide, polysulfone, epoxy resin, glass epoxy resin, melamine resin, phenol resin, urea resin, alkyd resin, fluororesin, polylactic acid, and other synthetic resins; copper, steel, aluminum, silicon, soda glass, alkali-free glass, indium tin oxide (ITO), and other inorganic materials; and paper, such as base paper, art paper, coated paper, cast coated paper, resin coated paper, and synthetic paper. The substrate may be one layer or two or more layers. When the substrate has two or more layers, two or more substrates made of different materials may be laminated.

[0019] The substrate is preferably in the form of a sheet or film. The thickness of the substrate is preferably 20 μm to 2000 μm. When the thickness of the substrate is 20 μm or more, the conductive ink film can be stably held, and the laminate on which the conductive ink film is formed can be easily handled.

[0020] The substrate may have an ink-receiving layer, and the thickness of the ink-receiving layer is preferably 1 μm to 20 μm. When the thickness of the ink-receiving layer is 1 μm to 20 μm, the ink-receiving layer can be more stably maintained, and the uniformity of the wet spread of the conductive ink is improved, thereby further improving the quality of the conductive ink film. The ink-receiving layer is a coating layer formed on the substrate to absorb and fix the ink.

[0021] In the conductive laminate of the present disclosure, from the viewpoints of insulation and adhesion, the substrate is preferably a glass substrate or a plastic substrate.

[0022] <Conductive ink film> In the conductive laminate of the present disclosure, the conductive ink film is provided on a substrate. Although other layers may be provided between the conductive ink film and the substrate, it is preferable that the conductive ink film is provided directly on the substrate.

[0023] In this disclosure, "conductive" means a material having a volume resistivity of 1×10 -2 This refers to the property of being less than Ω·cm.

[0024] In the conductive ink film, when the surface closer to the substrate is defined as the first main surface and the surface farther from the substrate is defined as the second main surface, the first porosity in the region from a 50% thickness position from the first main surface toward the second main surface to the second main surface is 15% to 50%, and the second porosity in the region from the first main surface toward the second main surface to a 10% thickness position is smaller than the first porosity.

[0025] Simply put, when the conductive ink film is divided into regions in the thickness direction, the first porosity in the non-substrate side 50% region far from the substrate is 15% to 50%, and the second porosity in the substrate side 10% region is smaller than the first porosity. When the first porosity is 15% or more, the heat dissipation is excellent. On the other hand, when the first porosity is 50% or less, the volume resistivity is reduced.

[0026] Furthermore, the second porosity being smaller than the first porosity means that the non-substrate side 50% region of the conductive ink film is coarser than the substrate side 10% region. When the non-substrate side 50% region is coarse, i.e., when the substrate side 10% region is dense, the volume resistivity decreases.

[0027] From the viewpoint of further improving the heat dissipation property, the first porosity is preferably 30% to 40%.

[0028] From the viewpoint of further reducing the volume resistivity, the second porosity is preferably 20% or less, more preferably 10% or less, and further preferably 7% or less. The lower limit of the second porosity is not particularly limited, and is, for example, 0%.

[0029] The difference between the first porosity and the second porosity is not particularly limited, but from the viewpoint of achieving both low volume resistivity and heat dissipation, it is preferably 5% to 40%, and more preferably 20% to 30%.

[0030] The porosity of the conductive ink film can be controlled by the type of conductive ink used to form the conductive ink film and the baking conditions after applying the conductive ink. For example, when ink containing metal particles is used as the conductive ink, voids are easily formed in the conductive ink film. When ink containing metal particles is used, the porosity decreases when the baking temperature is increased. Furthermore, the porosity decreases when the baking time is increased.

[0031] The porosity is measured, for example, by the following method.

[0032] The conductive laminate is cut in the thickness direction of the conductive laminate using a microtome (product name RM2255, manufactured by Leica) to obtain a cross section, and a cross section observation photograph is taken of the obtained cross section using a scanning electron microscope (product name S-4700, manufactured by HITACHI). The obtained cross-sectional observation photograph was binarized into white regions where conductive materials exist and black regions where voids exist by adjusting the threshold value using image software (Adobe Photoshop manufactured by Adobe Systems, Inc.). The position obtained by averaging the top 5 convex points and the bottom 5 concave points on the ink film surface side of the obtained image was determined as the top side. The position obtained by similar calculation on the ink film substrate side was determined as the bottom side. The area between the top side and the bottom side was divided into 10 equal parts, and the area from the bottom side to the first equal part was determined as the 10% area on the substrate side, and the area from the 5th equal part from the substrate side to the upper area was determined as the 50% area on the non-substrate side. The first porosity is calculated as the ratio of the area of ​​black regions (voids) to the area of ​​the entire region in the non-substrate side 50% region in the cross-section observation photograph. The second porosity is calculated as the ratio of the area of ​​black regions (voids) to the area of ​​the entire region in a 10% region on the substrate side in the cross-section observation photograph.

[0033] The conductive ink film preferably contains a conductive material, and the conductive material is preferably a metal. Examples of the metal include particles of base metals and precious metals. Examples of the base metal include nickel, titanium, cobalt, copper, chromium, manganese, iron, zirconium, tin, tungsten, molybdenum, and vanadium. Examples of the precious metal include gold, silver, platinum, palladium, iridium, osmium, ruthenium, rhodium, rhenium, and alloys containing these metals. From the viewpoint of conductivity, the conductive ink film preferably contains at least one selected from the group consisting of silver, gold, platinum, nickel, palladium, and copper, and more preferably contains silver.

[0034] The content of the metal in the conductive ink film is preferably 5% by mass to 70% by mass, and more preferably 7% by mass to 50% by mass, based on the total amount of the conductive ink film.

[0035] The thickness of the conductive ink film is not particularly limited, but from the viewpoints of productivity and conductivity, it is preferably 0.5 μm to 30 μm, and more preferably 5 μm to 20 μm.

[0036] [Method of manufacturing conductive laminate] The method for producing the conductive laminate of the present disclosure is not particularly limited as long as it is possible to form the above-mentioned conductive ink film on a substrate.

[0037] The conductive ink film can be formed, for example, by applying a conductive ink onto a substrate and then baking the conductive ink applied onto the substrate. The conductive ink film may be formed by repeating the application of the conductive ink and baking multiple times.

[0038] The conductive ink is preferably an ink containing metal particles (hereinafter also referred to as "metal particle ink"), an ink containing a metal complex (hereinafter also referred to as "metal complex ink"), or an ink containing a metal salt (hereinafter also referred to as "metal salt ink"), and is more preferably a metal particle ink or a metal complex ink.

[0039] <Metal particle ink> The metal particle ink is, for example, an ink composition in which metal particles are dispersed in a dispersion medium.

[0040] (metal particles) Examples of the metal constituting the metal particles include particles of base metals and precious metals. Examples of the base metals include nickel, titanium, cobalt, copper, chromium, manganese, iron, zirconium, tin, tungsten, molybdenum, and vanadium. Examples of the precious metals include gold, silver, platinum, palladium, iridium, osmium, ruthenium, rhodium, rhenium, and alloys containing these metals. Among them, from the viewpoint of electrical conductivity, the metal constituting the metal particles preferably includes at least one selected from the group consisting of silver, gold, platinum, nickel, palladium, and copper, and more preferably includes silver.

[0041] The average particle size of the metal particles is not particularly limited, but is preferably 10 nm to 500 nm, and more preferably 10 nm to 200 nm. When the average particle size is within the above range, the baking temperature of the metal particles is lowered, and the process suitability of the conductive ink film production is improved. In particular, when the metal particle ink is applied using a spray method or an inkjet recording method, the ejection property is improved, and the pattern formability and the uniformity of the film thickness of the conductive ink film tend to be improved. The average particle size here means the average value of the primary particle size of the metal particles (average primary particle size).

[0042] The average particle size of metal particles is calculated, for example, by measuring the 50% volume cumulative diameter (D50) three times using a laser diffraction / scattering particle size distribution analyzer (product name "LA-960", manufactured by Horiba, Ltd.) and averaging the values ​​obtained by the three measurements.

[0043] If necessary, the metal particle ink may contain metal particles having an average particle size of 500 nm or more. When metal particles having an average particle size of 500 nm or more are contained, the melting point of the nm-sized metal particles drops around the μm-sized metal particles, thereby bonding the conductive ink film.

[0044] The content of the metal particles in the metal particle ink is preferably 10% by mass to 90% by mass, and more preferably 20% by mass to 50% by mass, based on the total amount of the metal particle ink. When the content of the metal particles is 10% by mass or more, the volume resistivity is further reduced. When the content of the metal particles is 90% by mass or less, the ejection properties are improved when the metal particle ink is applied using a spray method or an inkjet recording method.

[0045] In addition to metal particles, the metal particle ink may contain, for example, a dispersant, a resin, a dispersion medium, a thickener, and a surface tension adjuster.

[0046] (Dispersant) The metal particle ink may contain a dispersant that adheres to at least a portion of the surface of the metal particles. The dispersant, together with the metal particles, essentially constitutes metal colloid particles. The dispersant has the effect of coating the metal particles to improve the dispersibility of the metal particles and prevent aggregation. The dispersant is preferably an organic compound capable of forming metal colloid particles. From the viewpoints of electrical conductivity and dispersion stability, the dispersant is preferably an amine compound, a carboxylic acid, or an alcohol.

[0047] The metal particle ink may contain one type of dispersant, or two or more types of dispersant.

[0048] Examples of the amine compound include saturated or unsaturated aliphatic amines. Among them, the amine compound is preferably an aliphatic amine having 4 to 8 carbon atoms. The aliphatic amine having 4 to 8 carbon atoms may be linear or branched, or may have a ring structure.

[0049] Aliphatic amines include, for example, butylamine, normal pentylamine, isopentylamine, hexylamine, 2-ethylhexylamine, and octylamine.

[0050] Examples of the amine having an alicyclic structure include cycloalkylamines such as cyclopentylamine and cyclohexylamine.

[0051] Aromatic amines include aniline.

[0052] The amine compound may have a functional group other than an amino group, such as a hydroxy group, a carboxy group, an alkoxy group, a carbonyl group, an ester group, or a mercapto group.

[0053] Examples of carboxylic acids include formic acid, oxalic acid, acetic acid, hexanoic acid, acrylic acid, octanoic acid, and oleic acid. A carboxyl group that is a part of a carboxylic acid may form a salt with a metal ion. The metal ion that forms the salt may be one type or two or more types.

[0054] The carboxylic acid may have a functional group other than the carboxy group, such as an amino group, a hydroxy group, an alkoxy group, a carbonyl group, an ester group, or a mercapto group.

[0055] Examples of the alcohol include terpene alcohol, allyl alcohol, oleyl alcohol, thianthic acid, ricinoleic acid, gallic acid, and salicylic acid. Alcohols are easily coordinated to the surfaces of metal particles, and can suppress aggregation of the metal particles.

[0056] Examples of the resin dispersant include dispersants that have a nonionic group as a hydrophilic group and can be uniformly dissolved in a solvent. Examples of the resin dispersant include polyvinylpyrrolidone, polyethylene glycol, polyethylene glycol-polypropylene glycol copolymer, polyvinyl alcohol, polyallylamine, and polyvinyl alcohol-polyvinyl acetate copolymer. The molecular weight of the resin dispersant is preferably 1000 to 50000, more preferably 1000 to 30000, in terms of weight average molecular weight.

[0057] The content of the dispersant in the metal particle ink is preferably 0.5% by mass to 50% by mass, and more preferably 1% by mass to 30% by mass, based on the total amount of the metal particle ink.

[0058] (dispersion medium) The metal particle ink preferably contains a dispersion medium. The type of the dispersion medium is not particularly limited, and examples thereof include hydrocarbons, alcohols, and water.

[0059] The dispersion medium contained in the metal particle ink may be one type or two or more types. The dispersion medium contained in the metal particle ink is preferably volatile. The boiling point of the dispersion medium is preferably 50°C to 250°C, more preferably 70°C to 220°C, and even more preferably 80°C to 200°C. When the boiling point of the dispersion medium is 50°C to 250°C, there is a tendency that both the stability and the sinterability of the metal particle ink can be achieved.

[0060] Hydrocarbons include aliphatic hydrocarbons and aromatic hydrocarbons.

[0061] Examples of the aliphatic hydrocarbon include saturated aliphatic hydrocarbons or unsaturated aliphatic hydrocarbons such as tetradecane, octadecane, heptamethylnonane, tetramethylpentadecane, hexane, heptane, octane, nonane, decane, tridecane, methylpentane, normal paraffin, and isoparaffin.

[0062] Aromatic hydrocarbons include, for example, toluene and xylene.

[0063] The alcohol includes aliphatic alcohols and alicyclic alcohols. When an alcohol is used as the dispersion medium, the dispersant is preferably an amine compound or a carboxylic acid.

[0064] Examples of the aliphatic alcohol include aliphatic alcohols having 6 to 20 carbon atoms which may contain an ether bond in the saturated or unsaturated chain, such as heptanol, octanol (e.g., 1-octanol, 2-octanol, 3-octanol, etc.), decanol (e.g., 1-decanol, etc.), lauryl alcohol, tetradecyl alcohol, cetyl alcohol, 2-ethyl-1-hexanol, octadecyl alcohol, hexadecenol, and oleyl alcohol.

[0065] Alicyclic alcohols include, for example, cycloalkanols such as cyclohexanol; terpene alcohols such as terpineol (including α, β, γ isomers, or any mixture thereof), dihydroterpineol; dihydroterpineol, myrtenol, sobrerol, menthol, carveol, perillyl alcohol, pinocarveol, sobrerol, and verbenol.

[0066] The dispersion medium may be water. From the viewpoint of adjusting physical properties such as viscosity, surface tension, and volatility, the dispersion medium may be a mixed solvent of water and another solvent. The other solvent to be mixed with water is preferably an alcohol. The alcohol used in combination with water is preferably an alcohol having a boiling point of 130° C. or less that is miscible with water. Examples of alcohol include 1-propanol, 2-propanol, 1-butanol, 2-butanol, tert-butanol, 1-pentanol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, and propylene glycol monomethyl ether.

[0067] The content of the dispersion medium in the metal particle ink is preferably 1% by mass to 50% by mass based on the total amount of the metal particle ink. If the content of the dispersion medium is 1% by mass to 50% by mass, sufficient conductivity as a conductive ink can be obtained. The content of the dispersion medium is more preferably 10% by mass to 45% by mass, and even more preferably 20% by mass to 40% by mass.

[0068] (resin) The metal particle ink may contain a resin, such as polyester, polyurethane, melamine resin, acrylic resin, styrene-based resin, polyether resin, or terpene resin.

[0069] The resin contained in the metal particle ink may be of one type or of two or more types.

[0070] The resin content in the metal particle ink is preferably 0.1% by mass to 5% by mass with respect to the total amount of the metal particle ink.

[0071] (Thickener) The metal particle ink may contain a thickener, such as clay minerals, bentonite, hectorite, etc.; cellulose derivatives, such as methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, etc.; and polysaccharides, such as xanthan gum, guar gum, etc.

[0072] The metal particle ink may contain one type of thickener, or two or more types of thickeners.

[0073] The content of the thickener in the metal particle ink is preferably 0.1% by mass to 5% by mass relative to the total amount of the metal particle ink.

[0074] (Surfactant) The metal particle ink may contain a surfactant, which makes it easier to form a uniform conductive ink film.

[0075] The surfactant may be any of anionic surfactants, cationic surfactants, and nonionic surfactants. Among them, the surfactant is preferably a fluorine-based surfactant from the viewpoint of being able to adjust the surface tension with a small content. In addition, the surfactant is preferably a compound having a boiling point of more than 250°C.

[0076] The viscosity of the metal particle ink is not particularly limited as long as it is 0.01 Pa·s to 5000 Pa·s, and preferably 0.1 Pa·s to 100 Pa·s. When the metal particle ink is applied using a spray method or an inkjet recording method, the viscosity of the metal particle ink is preferably 1 mPa·s to 100 mPa·s, more preferably 2 mPa·s to 50 mPa·s, and even more preferably 3 mPa·s to 30 mPa·s.

[0077] The viscosity of the metal particle ink is a value measured using a viscometer at 25° C. The viscosity is measured, for example, using a VISCOMETER TV-22 type viscometer (manufactured by Toki Sangyo Co., Ltd.).

[0078] The surface tension of the metal particle ink is not particularly limited, but is preferably 20 mN / m to 45 mN / m, and more preferably 25 mN / m to 40 mN / m. The surface tension is a value measured at 25° C. using a surface tensiometer. The surface tension is measured, for example, using a DY-700 (manufactured by Kyowa Interface Science Co., Ltd.).

[0079] (Metal Particle Manufacturing Method) The metal particles may be commercially available or may be produced by a known method. Examples of methods for producing metal particles include a wet reduction method, a gas phase method, and a plasma method. A preferred method for producing metal particles includes a wet reduction method that can produce metal particles with an average particle size of 200 nm or less with a narrow particle size distribution. Examples of methods for producing metal particles using a wet reduction method include a method including a step of mixing a metal salt and a reducing agent described in JP 2017-37761 A, WO 2014-57633 A, etc. to obtain a complexing reaction solution, and a step of heating the complexing reaction solution to reduce the metal ions in the complexing reaction solution and obtain a slurry of metal nanoparticles.

[0080] In the production of the metal particle ink, a heat treatment may be performed in order to adjust the content of each component contained in the metal particle ink to a predetermined range. The heat treatment may be performed under reduced pressure or under normal pressure. When the heat treatment is performed under normal pressure, the heat treatment may be performed in the air or in an inert gas atmosphere.

[0081] <Metal complex ink> The metal complex ink is, for example, an ink composition in which a metal complex is dissolved in a solvent.

[0082] Examples of the metal constituting the metal complex include silver, copper, gold, aluminum, magnesium, tungsten, molybdenum, zinc, nickel, iron, platinum, tin, copper, and lead. Among them, from the viewpoint of electrical conductivity, the metal constituting the metal complex preferably contains at least one selected from the group consisting of silver, gold, platinum, nickel, palladium, and copper, and more preferably contains silver.

[0083] The content of the metal contained in the metal complex ink is preferably 1% by mass to 40% by mass, more preferably 5% by mass to 30% by mass, and even more preferably 7% by mass to 20% by mass, calculated as the metal element, relative to the total amount of the metal complex ink.

[0084] The metal complex can be obtained, for example, by reacting a metal salt with a complexing agent. For example, a method of producing a metal complex includes adding a metal salt and a complexing agent to an organic solvent and stirring for a predetermined time. The stirring method is not particularly limited, and can be appropriately selected from known methods such as a method of stirring using a stirrer, a stirring blade or a mixer, a method of applying ultrasonic waves, etc.

[0085] Metal salts include oxides, thiocyanates, sulfides, chlorides, cyanides, cyanates, carbonates, acetates, nitrates, nitrites, sulfates, phosphates, perchlorates, tetrafluoroborates, acetylacetonate complexes, and carboxylates of metals.

[0086] Examples of the complexing agent include amine compounds, ammonium carbamate compounds, ammonium carbonate compounds, ammonium bicarbonate compounds, and carboxylic acids. Among them, from the viewpoint of electrical conductivity and stability of the metal complex, it is preferable that the complexing agent contains at least one selected from the group consisting of ammonium carbamate compounds, ammonium carbonate compounds, alkylamines, and carboxylic acids having 8 to 20 carbon atoms.

[0087] The metal complex has a structure derived from a complexing agent, and preferably has a structure derived from at least one selected from the group consisting of ammonium carbamate compounds, ammonium carbonate compounds, alkylamines, and carboxylic acids having 8 to 20 carbon atoms.

[0088] Examples of the amine compound that is a complexing agent include ammonia, primary amines, secondary amines, tertiary amines, and polyamines.

[0089] Examples of primary amines having a linear alkyl group include methylamine, ethylamine, 1-propylamine, n-butylamine, n-pentylamine, n-hexylamine, heptylamine, octylamine, nonylamine, n-decylamine, undecylamine, dodecylamine, tridecylamine, tetradecylamine, pentadecylamine, hexadecylamine, heptadecylamine, and octadecylamine.

[0090] Primary amines having branched alkyl groups include, for example, isopropylamine, sec-butylamine, tert-butylamine, isopentylamine, 2-ethylhexylamine, and tert-octylamine.

[0091] Examples of primary amines having an alicyclic structure include cyclohexylamine and dicyclohexylamine.

[0092] Examples of primary amines having a hydroxyalkyl group include ethanolamine, diethanolamine, triethanolamine, N-methylethanolamine, propanolamine, isopropanolamine, dipropanolamine, diisopropanolamine, tripropanolamine, and triisopropanolamine.

[0093] Examples of primary amines having an aromatic ring include benzylamine, N,N-dimethylbenzylamine, phenylamine, diphenylamine, triphenylamine, aniline, N,N-dimethylaniline, N,N-dimethyl-p-toluidine, 4-aminopyridine, and 4-dimethylaminopyridine.

[0094] Secondary amines include, for example, dimethylamine, diethylamine, dipropylamine, dibutylamine, diphenylamine, dicyclopentylamine, and methylbutylamine.

[0095] Tertiary amines include, for example, trimethylamine, triethylamine, tripropylamine, and triphenylamine.

[0096] Polyamines include, for example, ethylenediamine, 1,3-diaminopropane, diethylenetriamine, triethylenetetramine, tetramethylenepentamine, hexamethylenediamine, tetraethylenepentamine, and combinations thereof.

[0097] The amine compound is preferably an alkylamine, more preferably an alkylamine having 3 to 10 carbon atoms, and more preferably a primary alkylamine having 4 to 10 carbon atoms.

[0098] The amine compound constituting the metal complex may be one type or two or more types.

[0099] When reacting a metal salt with an amine compound, the molar ratio of the amine compound to the molar amount of the metal salt is preferably 1 to 15, and more preferably 1.5 to 6. When the ratio is within the above range, the complex formation reaction is completed, and a transparent solution is obtained.

[0100] Examples of the ammonium carbamate-based compound that is a complexing agent include ammonium carbamate, methylammonium methylcarbamate, ethylammonium ethylcarbamate, 1-propylammonium 1-propylcarbamate, isopropylammonium isopropylcarbamate, butylammonium butylcarbamate, isobutylammonium isobutylcarbamate, amylammonium amylcarbamate, hexylammonium hexylcarbamate, heptylammonium heptylcarbamate, octylammonium octylcarbamate, 2-ethylhexylammonium 2-ethylhexylcarbamate, nonylammonium nonylcarbamate, and decylammonium decylcarbamate.

[0101] Examples of the ammonium carbonate-based compound that is a complexing agent include ammonium carbonate, methyl ammonium carbonate, ethyl ammonium carbonate, 1-propyl ammonium carbonate, isopropyl ammonium carbonate, butyl ammonium carbonate, isobutyl ammonium carbonate, amyl ammonium carbonate, hexyl ammonium carbonate, heptyl ammonium carbonate, octyl ammonium carbonate, 2-ethylhexyl ammonium carbonate, nonyl ammonium carbonate, and decyl ammonium carbonate.

[0102] Examples of the ammonium bicarbonate-based compound that is a complexing agent include ammonium bicarbonate, methylammonium bicarbonate, ethylammonium bicarbonate, 1-propylammonium bicarbonate, isopropylammonium bicarbonate, butylammonium bicarbonate, isobutylammonium bicarbonate, amylammonium bicarbonate, hexylammonium bicarbonate, heptylammonium bicarbonate, octylammonium bicarbonate, 2-ethylhexylammonium bicarbonate, nonylammonium bicarbonate, and decylammonium bicarbonate.

[0103] When reacting a metal salt with an ammonium carbamate compound, an ammonium carbonate compound, or an ammonium bicarbonate compound, the ratio of the molar amount of the ammonium carbamate compound, the ammonium carbonate compound, or the ammonium bicarbonate compound to the molar amount of the metal salt is preferably 0.01 to 1 times, and more preferably 0.05 to 0.6 times.

[0104] Examples of the carboxylic acid that is a complexing agent include caproic acid, caprylic acid, pelargonic acid, 2-ethylhexanoic acid, capric acid, neodecanoic acid, undecanoic acid, lauric acid, myristic acid, palmitic acid, stearic acid, palmitoleic acid, oleic acid, linoleic acid, and linolenic acid. Among them, the carboxylic acid is preferably a carboxylic acid having 8 to 20 carbon atoms, and more preferably a carboxylic acid having 10 to 16 carbon atoms.

[0105] The content of the metal complex in the metal complex ink is preferably 5% by mass to 90% by mass, and more preferably 10% by mass to 40% by mass, based on the total amount of the metal complex ink. When the content of the metal complex is 10% by mass or more, the volume resistivity is further reduced. When the content of the metal complex is 90% by mass or less, the ejection properties are improved when the metal particle ink is applied using a spray method or an inkjet recording method.

[0106] (solvent) The metal complex ink preferably contains a solvent. The solvent is not particularly limited as long as it can dissolve the components contained in the metal complex ink, such as the metal complex. From the viewpoint of ease of production, the solvent preferably has a boiling point of 30°C to 300°C, more preferably 50°C to 200°C, and even more preferably 50°C to 150°C.

[0107] The content of the solvent in the metal complex ink is preferably such that the concentration of metal ions relative to the metal complex (the amount of metal present as free ions per gram of metal complex) is 0.01 mmol / g to 3.6 mmol / g, more preferably 0.05 mmol / g to 2 mmol / g. When the concentration of metal ions is within the above range, the metal complex ink has excellent fluidity and can obtain electrical conductivity.

[0108] Examples of the solvent include hydrocarbons, cyclic hydrocarbons, aromatic hydrocarbons, carbamates, alkenes, amides, ethers, esters, alcohols, thiols, thioethers, phosphines, and water. The solvent contained in the metal complex ink may be one type only, or two or more types.

[0109] The hydrocarbon is preferably a linear or branched hydrocarbon having a carbon number of 6 to 20. Examples of the hydrocarbon include pentane, hexane, heptane, octane, nonane, decane, undecane, dodecane, tridecane, tetradecane, pentadecane, hexadecane, octadecane, nonadecane, and icosane.

[0110] The cyclic hydrocarbon is preferably a cyclic hydrocarbon having a carbon number of 6 to 20. Examples of the cyclic hydrocarbon include cyclohexane, cycloheptane, cyclooctane, cyclononane, cyclodecane, and decalin.

[0111] Aromatic hydrocarbons include, for example, benzene, toluene, xylene, and tetralin.

[0112] The ether may be any of linear ethers, branched ethers, and cyclic ethers, and examples of the ether include diethyl ether, dipropyl ether, dibutyl ether, methyl t-butyl ether, tetrahydrofuran, tetrahydropyran, dihydropyran, and 1,4-dioxane.

[0113] The alcohol may be a primary alcohol, a secondary alcohol, or a tertiary alcohol.

[0114] Examples of alcohols include ethanol, 1-propanol, 2-propanol, 1-methoxy-2-propanol, 1-butanol, 2-butanol, 1-pentanol, 2-pentanol, 3-pentanol, 1-hexanol, 2-hexanol, 3-hexanol, 1-octanol, 2-octanol, 3-octanol, tetrahydrofurfuryl alcohol, cyclopentanol, terpineol, decanol, isodecyl alcohol, lauryl alcohol, isolauryl alcohol, myristyl alcohol, isomyristyl alcohol, cetyl alcohol (cetanol), isocetyl alcohol, stearyl alcohol, isostearyl alcohol, oleyl alcohol, isooleyl alcohol, linolyl alcohol, isolinolyl alcohol, palmityl alcohol, isopalmityl alcohol, eicosyl alcohol, and isoeicosyl alcohol.

[0115] Ketones include, for example, acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone.

[0116] Examples of esters include methyl acetate, ethyl acetate, isopropyl acetate, butyl acetate, isobutyl acetate, sec-butyl acetate, methoxybutyl acetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monobutyl ether acetate, dipropylene glycol monomethyl ether acetate, dipropylene glycol monoethyl ether acetate, dipropylene glycol monobutyl ether acetate, and 3-methoxybutyl acetate.

[0117] (reducing agent) The metal complex ink may contain a reducing agent, which promotes the reduction of the metal complex to a metal.

[0118] Examples of reducing agents include metal borohydrides, aluminum hydrides, amine compounds, alcohols, organic acids, reducing sugars, sugar alcohols, sodium sulfite, hydrazine compounds, dextrin, hydroquinone, hydroxylamine, ethylene glycol, glutathione, and oxime compounds.

[0119] The reducing agent may be an oxime compound described in JP-A-2014-516463. Examples of the oxime compound include acetone oxime, cyclohexanone oxime, 2-butanone oxime, 2,3-butanedione monoxime, dimethylglyoxime, methyl acetoacetate monoxime, methyl pyruvate monoxime, benzaldehyde oxime, 1-indanone oxime, 2-adamantanone oxime, 2-methylbenzamide oxime, 3-methylbenzamide oxime, 4-methylbenzamide oxime, 3-aminobenzamide oxime, 4-aminobenzamide oxime, acetophenone oxime, benzamide oxime, and pinacolone oxime.

[0120] The reducing agent contained in the metal complex ink may be of one type or of two or more types.

[0121] The content of the reducing agent in the metal complex ink is not particularly limited, but is preferably 0.1% to 20% by mass, more preferably 0.3% to 10% by mass, and even more preferably 1% to 5% by mass.

[0122] (resin) The metal complex ink may contain a resin. When the metal complex ink contains a resin, the adhesion of the metal complex ink to the substrate is improved.

[0123] Examples of the resin include polyester, polyethylene, polypropylene, polyacetal, polyolefin, polycarbonate, polyamide, fluororesin, silicone resin, ethyl cellulose, hydroxyethyl cellulose, rosin, acrylic resin, polyvinyl chloride, polysulfone, polyvinylpyrrolidone, polyvinyl alcohol, polyvinyl resin, polyacrylonitrile, polysulfide, polyamideimide, polyether, polyarylate, polyether ether ketone, polyurethane, epoxy resin, vinyl ester resin, phenol resin, melamine resin, and urea resin.

[0124] The resin contained in the metal complex ink may be of one type or of two or more types.

[0125] (Additives) The metal complex ink may further contain additives such as inorganic salts, organic salts, inorganic oxides such as silica, surface conditioners, wetting agents, crosslinking agents, antioxidants, rust inhibitors, heat stabilizers, surfactants, plasticizers, hardeners, thickeners, silane coupling agents, etc., within the scope of not impairing the effects of the present disclosure. The total content of the additives in the metal complex ink is preferably 20% by mass or less with respect to the total amount of the metal complex ink.

[0126] The viscosity of the metal complex ink is not particularly limited as long as it is 0.01 Pa·s to 5000 Pa·s, and preferably 0.1 Pa·s to 100 Pa·s. When the metal complex ink is applied using a spray method or an inkjet recording method, the viscosity of the metal complex ink is preferably 1 mPa·s to 100 mPa·s, more preferably 2 mPa·s to 50 mPa·s, and even more preferably 3 mPa·s to 30 mPa·s.

[0127] The viscosity of the metal complex ink is a value measured using a viscometer at 25° C. The viscosity is measured, for example, using a VISCOMETER TV-22 type viscometer (manufactured by Toki Sangyo Co., Ltd.).

[0128] The surface tension of the metal complex ink is not particularly limited, and is preferably 20 mN / m to 45 mN / m, and more preferably 25 mN / m to 35 mN / m. The surface tension is a value measured at 25° C. using a surface tensiometer. The surface tension is measured, for example, using a DY-700 (manufactured by Kyowa Interface Science Co., Ltd.).

[0129] <Metal salt ink> The metal salt ink is, for example, an ink composition in which a metal salt is dissolved in a solvent.

[0130] Examples of metals constituting the metal salt include silver, copper, gold, aluminum, magnesium, tungsten, molybdenum, zinc, nickel, iron, platinum, tin, copper, and lead. Among these, from the viewpoint of electrical conductivity, the metal constituting the metal complex preferably contains at least one selected from the group consisting of silver, gold, platinum, nickel, palladium, and copper, and more preferably contains silver.

[0131] The content of metal contained in the metal salt ink is preferably 1% by mass to 40% by mass, more preferably 5% by mass to 30% by mass, and even more preferably 7% by mass to 20% by mass, calculated as metal element, relative to the total amount of the metal salt ink.

[0132] Examples of metal salts include metal benzoates, halides, carbonates, citrates, iodates, nitrites, nitrates, acetates, phosphates, sulfates, sulfides, trifluoroacetates, and carboxylates. Two or more types of salts may be used in combination.

[0133] From the viewpoints of electrical conductivity and storage stability, the metal salt is preferably a metal carboxylate. The carboxylic acid forming the carboxylate is preferably at least one selected from the group consisting of formic acid and fatty acids having 1 to 30 carbon atoms. When the carboxylic acid is a fatty acid having 1 to 30 carbon atoms, the fatty acid may be linear or branched, and may have a substituent.

[0134] Straight chain fatty acids include, for example, acetic acid, propionic acid, butyric acid, valeric acid, pentanoic acid, hexanoic acid, heptanoic acid, behenic acid, oleic acid, octanoic acid, nonanoic acid, decanoic acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, capric acid, and undecanoic acid.

[0135] Examples of branched fatty acids include isobutyric acid, isovaleric acid, ethylhexanoic acid, neodecanoic acid, pivalic acid, 2-methylpentanoic acid, 3-methylpentanoic acid, 4-methylpentanoic acid, 2,2-dimethylbutanoic acid, 2,3-dimethylbutanoic acid, 3,3-dimethylbutanoic acid, and 2-ethylbutanoic acid.

[0136] Examples of substituted carboxylic acids include hexafluoroacetylacetonate, hydroangelic acid, 3-hydroxybutyric acid, 2-methyl-3-hydroxybutyric acid, 3-methoxybutyric acid, acetonedicarboxylic acid, 3-hydroxyglutaric acid, 2-methyl-3-hydroxyglutaric acid, and 2,2,4,4-hydroxyglutaric acid.

[0137] The metal salt may be a commercially available product or may be produced by a known method. The silver salt is produced, for example, by the following method.

[0138] First, a silver compound (e.g., silver acetate) that serves as a silver supply source and an equal amount of formic acid or fatty acid having 1 to 30 carbon atoms to the molar equivalent of the silver compound are added to an organic solvent such as ethanol. The mixture is stirred for a predetermined time using an ultrasonic stirrer, and the resulting precipitate is washed with ethanol and decanted. All of these steps can be performed at room temperature. The mixing ratio of the silver compound to the formic acid or fatty acid having 1 to 30 carbon atoms is preferably 1:2 to 2:1 in molar ratio, and more preferably 1:1.

[0139] The metal salt ink may contain a solvent, a reducing agent, a resin, and an additive. Preferred aspects of the solvent, reducing agent, resin, and additive are the same as those of the solvent, reducing agent, resin, and additive that may be contained in the metal complex ink.

[0140] The viscosity of the metal salt ink is not particularly limited as long as it is 0.01 Pa·s to 5000 Pa·s, and preferably 0.1 Pa·s to 100 Pa·s. When the metal salt ink is applied using a spray method or an inkjet recording method, the viscosity of the metal salt ink is preferably 1 mPa·s to 100 mPa·s, more preferably 2 mPa·s to 50 mPa·s, and even more preferably 3 mPa·s to 30 mPa·s.

[0141] The viscosity of the metal salt ink is a value measured using a viscometer at 25° C. The viscosity is measured, for example, using a VISCOMETER TV-22 type viscometer (manufactured by Toki Sangyo Co., Ltd.).

[0142] The surface tension of the metal salt ink is not particularly limited, and is preferably 20 mN / m to 45 mN / m, and more preferably 25 mN / m to 35 mN / m. The surface tension is a value measured at 25° C. using a surface tensiometer. The surface tension is measured, for example, using a DY-700 (manufactured by Kyowa Interface Science Co., Ltd.).

[0143] The method for producing a conductive laminate according to the present disclosure includes a step of applying at least one type of conductive ink selected from the group consisting of the metal particle ink, the metal complex ink, and the metal salt ink onto a substrate, and a step of baking the applied conductive ink. It is preferable that the step of applying the conductive ink and the step of baking are repeated two or more times. In addition, in the method for producing a conductive laminate according to the present disclosure, the conductive ink may be applied multiple times and then baked. In particular, in order to obtain a conductive laminate having a first porosity of 15% to 50% and a second porosity smaller than the first porosity, it is preferable that the method for producing a conductive laminate according to the present disclosure includes a step of applying the metal complex ink onto a substrate and baking the metal complex ink.

[0144] Preferred aspects of the method for producing a conductive laminate according to the present disclosure include the following aspects.

[0145] (1) A method of performing a step of applying a metal complex ink, a baking step, a step of applying a metal particle ink, and a baking step in this order. (2) A method of performing a step of applying a metal complex ink, a baking step, a step of applying a metal complex ink, and a baking step in this order. (3) A method of performing a step of applying a metal complex ink, a baking step, a step of applying a metal complex ink, a baking step, a step of applying a metal particle ink, and a baking step in this order. (4) A method of performing a step of applying a metal particle ink, a baking step, a step of applying a metal particle ink, a baking step, a step of applying a metal particle ink, and a baking step in this order. (5) A method of performing a step of applying a metal complex ink, a baking step, a step of applying a metal complex ink, a baking step, a step of applying a metal complex ink, a baking step, a step of applying a metal particle ink, and a baking step in this order. (6) A method of performing a step of applying a metal complex ink, a baking step, a step of applying a metal complex ink, a baking step, a step of applying a metal complex ink, a baking step, a step of applying a metal particle ink, and a baking step in this order. (7) A method of performing a step of applying a metal complex ink, a baking step, a step of applying a metal particle ink, a baking step, a step of applying a metal particle ink, a baking step, a step of applying a metal particle ink, and a baking step in this order.

[0146] In a preferred embodiment of the above manufacturing method, when the step of applying a metal complex ink is included two or more times, the metal complex inks used in each step may be the same or different. Also, in the above manufacturing method, when the step of applying a metal particle ink is included two or more times, the metal particle inks used in each step may be the same or different. Note that, "two inks are the same" means that the types and amounts of components contained in the inks are the same, and "two inks are different" means that at least one of the types and amounts of components contained in the inks is different from each other.

[0147] In a preferred embodiment of the above-mentioned production method, the firing temperature and firing time in each firing step may be the same or different.

[0148] In particular, the manufacturing method of the conductive laminate of the present disclosure preferably includes a step of applying a first conductive ink containing a metal complex onto a substrate (hereinafter referred to as the "first application step"), a step of baking the first conductive ink (hereinafter referred to as the "first baking step"), a step of applying a second conductive ink containing metal particles onto the baked first conductive ink (hereinafter referred to as the "second application step"), and a step of baking the second conductive ink (hereinafter referred to as the "second baking step").

[0149] (First application step) The first application step is a step of applying a first conductive ink containing a metal complex onto a substrate, the details of which are as described above.

[0150] The method for applying the first conductive ink onto the substrate is not particularly limited, and examples thereof include known methods such as a coating method, an inkjet recording method, a dipping method, etc. Among these, from the viewpoint of being able to reduce the thickness of the conductive ink film by ejecting a small amount of ink, it is preferable to apply the first conductive ink using the inkjet recording method in the first application step.

[0151] The inkjet recording method may be any of the following: a charge control method that uses electrostatic attraction to eject ink; a drop-on-demand method (pressure pulse method) that uses the vibration pressure of a piezoelectric element; an acoustic inkjet method in which an electric signal is converted into an acoustic beam and irradiated onto the ink to eject the ink using radiation pressure; and a thermal inkjet (Bubble Jet (registered trademark)) method in which ink is heated to form bubbles and the resulting pressure is utilized.

[0152] As an inkjet recording method, in particular, the method described in JP-A-54-59936 can be effectively utilized, in which ink undergoes a sudden change in volume when subjected to the action of thermal energy, and the ink is ejected from a nozzle by the force resulting from this change in state.

[0153] In addition, for the inkjet recording method, the method described in paragraphs 0093 to 0105 of JP-A No. 2003-306623 can also be referred to.

[0154] Inkjet heads used in inkjet recording methods include a shuttle method, in which a short serial head is used and recording is performed while the head is scanned in the width direction of the substrate, and a line method, in which a line head is used in which recording elements are arranged to correspond to the entire area of ​​one side of the substrate.

[0155] In the line method, a pattern can be formed over the entire surface of a substrate by scanning the substrate in a direction intersecting the arrangement direction of the recording elements, and a transport system such as a carriage for scanning a short head is not required.

[0156] Furthermore, since complicated scanning control of the carriage movement and the substrate is not required and only the substrate moves, a higher formation speed can be achieved compared to the shuttle method.

[0157] The droplet volume of the first conductive ink ejected from the inkjet head is preferably 1 pL (picoliter) to 100 pL, more preferably 3 pL to 80 pL, and even more preferably 3 pL to 20 pL.

[0158] In the first application step, the temperature of the substrate when the first conductive ink is applied is preferably 20° C. to 120° C., and more preferably 40° C. to 80° C. When the substrate temperature is 20° C. to 120° C., the influence of heat-induced deformation of the substrate and the like is small, and drying of the ink is promoted.

[0159] (First firing process) The first baking step is a step of baking the first conductive ink.

[0160] In the first firing step, the firing temperature is preferably 250° C. or lower, and the firing time is preferably 1 minute to 120 minutes.

[0161] The baking temperature is more preferably 50° C. to 200° C., and even more preferably 60° C. to 120° C. The baking time is more preferably 1 minute to 40 minutes. When the baking temperature and baking time are within the above ranges, it is possible to bake the ink with minimal effects such as deformation of the substrate due to heat.

[0162] The porosity of the conductive ink film can be adjusted by the baking temperature and baking time. For example, a lower baking temperature tends to result in a higher porosity.

[0163] The method of firing is not particularly limited, and can be any known method.

[0164] The time from the end of the first application step to the start of the first baking step is preferably 60 seconds or less. The lower limit of the time is not particularly limited, but is, for example, 1 microsecond. If the time is 60 seconds or less, the ink is prevented from spreading, and a thick film is easily formed.

[0165] The "point in time when the first application step is completed" refers to the point in time when all of the ink droplets of the first conductive ink have landed on the substrate. The "point in time when the first firing step is started" refers to the point in time when the base material is placed in the firing step device and heating is started.

[0166] (Second application step) The second application step is a step of applying a second conductive ink containing metal particles onto the fired first conductive ink.

[0167] The method of applying the second conductive ink onto the baked first conductive ink is not particularly limited, and examples thereof include known methods such as a coating method, an inkjet recording method, and a dipping method. Among them, from the viewpoint of being able to reduce the thickness of the conductive ink film by ejecting a small amount of ink, it is preferable to apply the second conductive ink using an inkjet recording method in the second application step. Details of the inkjet recording method are as described above.

[0168] In the second application step, the temperature of the substrate when the second conductive ink is applied is preferably 20° C. to 120° C., and more preferably 40° C. to 80° C. When the substrate temperature is 20° C. to 120° C., the influence of heat-induced deformation of the substrate and the like is small, and drying of the ink is promoted.

[0169] (Second firing process) The second baking step is a step of baking the second conductive ink.

[0170] In the second baking step, the baking temperature is preferably 250° C. or less and the baking time is preferably 1 to 120 minutes. When the baking temperature and baking time are within the above ranges, it is possible to bake the ink while reducing the influence of heat-induced deformation of the substrate, etc.

[0171] The baking temperature is more preferably 50° C. to 200° C., and further preferably 60° C. to 120° C. The baking time is more preferably 1 minute to 40 minutes.

[0172] The method of firing is not particularly limited, and can be any known method. EXAMPLES

[0173] Hereinafter, the present disclosure will be described more specifically with reference to examples. However, the present disclosure is not limited to the following examples as long as it does not depart from the gist of the disclosure.

[0174] <Preparation of conductive ink (silver particle ink)> (1) Silver particle ink A1 -Preparation of silver particle dispersion 1- Solution a was prepared by dissolving 6.8 g of polyvinylpyrrolidone (weight average molecular weight 3000, manufactured by Sigma-Aldrich) in 100 mL of water as a dispersant. Separately, solution b was prepared by dissolving 50.00 g of silver nitrate in 200 mL of water. Solution a and solution b were mixed and stirred, and 78.71 g of 85 mass% N,N-diethylhydroxylamine aqueous solution was dropped at room temperature into the resulting mixture, and further, a solution in which 6.8 g of polyvinylpyrrolidone was dissolved in 1000 mL of water was slowly dropped at room temperature. The resulting suspension was passed through an ultrafiltration unit (Vivaflow 50 manufactured by Sartorius-Stedim, molecular weight cutoff: 100,000, number of units: 4), and purified by passing purified water through it until about 5 L of exudate was discharged from the ultrafiltration unit. The supply of purified water was stopped, and the mixture was concentrated to obtain 30 g of silver particle dispersion 1. The solid content in this dispersion was 50% by mass, and the silver content in the solid content was measured by TG-DTA (thermogravimetry and differential thermal analysis) (manufactured by Hitachi High-Tech Corporation, model: STA7000 series) and found to be 96.0% by mass. The obtained silver particle dispersion 1 was diluted 20 times with ion-exchanged water and measured using a particle size analyzer FPAR-1000 (manufactured by Otsuka Electronics Co., Ltd.) to determine the volume average particle size of the silver particles. The volume average particle size of silver particle dispersion 1 was 60 nm. -Adjustment of Silver Particle Ink A1- 2 g of 2-propanol and 0.1 g of Olfin E-1010 (manufactured by Nissin Chemical Industry Co., Ltd.) as a surfactant were added to 10 g of the silver particle dispersion, and water was added so that the silver concentration became 40 mass %, to obtain a conductive ink A1.

[0175] (2) Silver particle ink A2 -Preparation of silver particle dispersion 2- Silver particle dispersion 2 was prepared in the same manner as silver particle dispersion 1, except that the dispersant in silver particle dispersion 1 was changed to polyvinylpyrrolidone (weight average molecular weight 6000, manufactured by Sigma-Aldrich) and the amount of polyvinylpyrrolidone added was changed from 6.8 g to 7.4 g. The volume particle diameter of silver particle dispersion 2 was 100 nm. -Preparation of silver particle ink A2- Silver particle ink A2 was prepared in the same manner as silver particle ink A1, except that silver particle dispersion liquid 2 was used instead of silver particle dispersion liquid 1.

[0176] <Preparation of conductive ink (silver complex ink)> (1) Silver complex ink B1 5.0 g of 1-propanol, 0.17 g of silver acetate, and 0.05 g of formic acid were added to a 50 mL three-neck flask and stirred for 20 minutes. The resulting silver salt precipitate was decanted three times with 1-propanol and washed. 0.12 g of 1-propylamine and 5.0 g of 1-propanol were added to the precipitate and stirred for 30 minutes. Next, 1.0 g of water was added and further stirred to obtain a solution containing a silver complex. This solution was filtered using a PTFE (polytetrafluoroethylene) membrane filter with a pore size of 0.45 μm to obtain silver complex ink B1.

[0177] (2) Silver complex ink B2 In a 50 mL three-neck flask, 6.08 g of isobutylammonium carbonate and 15.0 g of isopropyl alcohol were added and dissolved. Next, 2.0 g of silver oxide was added and reacted at room temperature for 2 hours to obtain a uniform solution. Furthermore, 0.3 g of 2-hydroxy-2-methylpropylamine was added and stirred to obtain a solution containing a silver complex. This solution was filtered using a PTFE (polytetrafluoroethylene) membrane filter with a pore size of 0.45 μm to obtain silver complex ink B2.

[0178] (3) Silver complex ink B3 2.5g of silver neodecanoate, 5g of xylene, and 3.0g of terpineol were added to a 25mL three-neck flask and dissolved. Then, 1g of tert-octylamine was added and stirred to obtain a solution containing a silver complex. The mixture was reacted at room temperature for 2 hours to obtain a uniform solution. This solution was filtered using a PTFE (polytetrafluoroethylene) membrane filter with a pore size of 0.45 μm to obtain silver complex ink B3.

[0179] (4) Silver complex ink B4 5.0 g of water, 1.0 g of silver acetate, 1.0 g of ethylenediamine, and 1.0 g of amylamine were added to a 25 mL three-neck flask and stirred for 20 minutes. 0.2 g of formic acid was added to the resulting solution and stirred for an additional 30 minutes to obtain a solution containing a silver complex. This solution was filtered using a PTFE (polytetrafluoroethylene) membrane filter with a pore size of 0.45 μm to obtain silver complex ink B4.

[0180] <Preparation of conductive ink (silver halide ink)> Silver halide ink C1 4 g of silver neodecanoate was added to a 50 mL three-neck flask. Next, 3.0 g of trimethylbenzene and 3.0 g of terpineol were added and stirred to obtain a solution containing a silver complex. This solution was filtered using a PTFE (polytetrafluoroethylene) membrane filter with a pore size of 0.45 μm to obtain a silver salt ink C1.

[0181] [Example 1] A polyethylene terephthalate film (product name "Viewful UV TP-100", manufactured by Kimoto Co., Ltd.) was prepared as a substrate. The silver complex ink B1 was filled into an ink cartridge (for 10 picoliters) for an inkjet recording device (product name "DMP-2850", manufactured by FUJIFILM DIMATIX Co., Ltd.). The image recording conditions were a resolution of 600 dpi (dots per inch) and a droplet volume of 10 picoliters per dot. The substrate was preheated to 40°C, and a solid image with a width of 5 cm and a length of 10 cm was recorded on the substrate at 40°C (application process 1). After 1 second had elapsed from the time when the last ink droplet of the silver complex ink B1 landed on the substrate, the solid image was heated at 150°C for 20 minutes using a hot plate (baking process 1). As a result, a conductive ink film with metallic luster was formed on the substrate.

[0182] Next, the silver particle ink A2 was filled into an ink cartridge (for 10 picoliters) for an inkjet recording device (product name "DMP-2850", manufactured by FUJIFILM DIMATIX). The substrate on which the conductive ink film was formed using the silver complex ink B1 was held at 20°C in advance, and a solid image was recorded on the substrate at 20°C under the same conditions as the image recording conditions described above so as to overlap the solid image (application step 2). The solid image was heated at 160°C for 20 minutes using a hot plate to obtain a conductive laminate on which a conductive ink film with a thickness of 7 μm and metallic luster was formed (baking step 2).

[0183] [Examples 2 to 16 and Comparative Examples 1 to 6] In Examples 2 to 16 and Comparative Examples 1 to 6, conductive laminates were obtained in the same manner as in Example 1, except that the type of conductive ink, the temperature of the substrate, the baking temperature, and the baking time were changed to the conditions shown in Tables 1 and 2. Each treatment was performed in the order of application step 1, baking step 1, application step 2, baking step 2, application step 3, baking step 3, application step 4, and baking step 4. For Examples and Comparative Examples in which the treatment was completed at baking step 2, "-" is entered after application step 3 in the table. The thickness (film thickness) of the conductive ink film in each conductive laminate is also listed in the table. It should be noted that Examples 4, 10, and 11 are reference examples.

[0184] In addition, in Comparative Example 6, since the firing temperature in the firing step 1 was low, the silver was not sufficiently fired, and the conductive ink film formed on the substrate was black in color.

[0185] The conductive laminates obtained in each of the Examples and Comparative Examples were used to measure the first porosity and the second porosity, and were evaluated for volume resistivity and heat dissipation. The measurement results and evaluation results are shown in the table.

[0186] <Measurement of first porosity and second porosity> The conductive laminate was cut in the thickness direction of the conductive laminate using a microtome (product name RM2255, manufactured by Leica) to obtain a cross section, and a cross section observation photograph was taken of the obtained cross section using a scanning electron microscope (product name S-4700, manufactured by HITACHI). The obtained cross-sectional observation photograph was binarized into white areas where conductive materials exist and black areas where voids exist by adjusting the threshold value using image software (Adobe Photoshop manufactured by Adobe Systems, Inc.). The position obtained by averaging the top 5 convex parts and the bottom 5 concave parts on the ink film surface side of the obtained image was determined as the top side. The position obtained by similar calculation on the ink film substrate side was determined as the bottom side. The area between the top side and the bottom side was divided into 10 equal parts, and the area from the bottom side to the first equal part was determined as the 10% area on the substrate side, and the area from the 5th equal part from the substrate side to the upper area was determined as the 50% area on the non-substrate side. The first porosity was calculated as the ratio of the area of ​​black regions (voids) to the area of ​​the entire region in the non-substrate 50% region in the cross-section observation photograph. The second porosity was calculated as the ratio of the area of ​​black regions (voids) to the area of ​​the entire region in a 10% region on the substrate side in the cross-section observation photograph.

[0187] <Evaluation of volume resistivity> A print pattern was formed on the surface of the conductive ink film so that it had a size of 5 cm x 10 cm, and an evaluation sample was obtained. The volume resistivity [Ω·cm] of the conductive ink film in the evaluation sample was measured at room temperature (23°C) using a resistivity meter (product name "Loresta GP", manufactured by Mitsubishi Chemical Analytech Co., Ltd.) by the four-terminal method. The evaluation criteria are as follows. Rank 2 or higher is a level that is not problematic for practical use. 5: Volume resistivity is 5×10 -6 It is less than Ω cm. 4: Volume resistivity is 5×10 -6 Ω cm or more 1×10 -5 It is less than Ω·cm. 3: Volume resistivity is 1×10 -5 Ω cm or more 5×10 -5 It is less than Ω cm. 2: Volume resistivity is 5×10 -5 Ω cm or more 1×10 -4 It is less than Ω·cm. 1: Volume resistivity is 1×10 -4 Ω·cm or more.

[0188] <Evaluation of heat dissipation> A print pattern was formed on the surface of the conductive ink film so that it had a size of 5 cm x 10 cm, and an evaluation sample was obtained. The ratio P of the heat transmission rate Q1 of each evaluation sample to the heat transmission rate Q0 of the experimental metal plate (product name "B-29 silver plate", purity 99.99%, manufactured by Kenis Co., Ltd.) was calculated. The heat transmission rate was calculated based on the following formula X. P=Q1 / Q0 Heat transmission amount = (T h -T c )×Aλ / L …(X) In formula X, T h is the hot fluid temperature (℃), T h is the low-temperature fluid temperature (℃), A is the surface area of ​​the membrane (m 2 ), λ is the thermal conductivity of the film (W / (m K), and L is the film thickness (m). Heat dissipation was evaluated based on the ratio P. The evaluation criteria are as follows. The larger P is, the better the heat dissipation is. Rank 2 or higher is a level that is not problematic in practical use. 5: P is 2.0 or higher. 4: P is 1.7 or greater but less than 2. 3: P is 1.5 or greater but less than 1.7. 2: P is greater than or equal to 1.0 and less than 1.5. 1:P is less than 1.0.

[0189] [Table 1]

[0190] [Table 2]

[0191] [Table 3]

[0192] As shown in Tables 1 and 2, Examples 1 to 16 each comprised a substrate and a conductive ink film provided on the substrate, and when the surface of the conductive ink film closer to the substrate is defined as the first main surface and the surface farther from the substrate is defined as the second main surface, the first porosity in the region from the 50% thickness position from the first main surface toward the second main surface to the second main surface was 15% to 50%, and the second porosity in the region from the first main surface to the 10% thickness position toward the second main surface was smaller than the first porosity. As a result, it was found that the volume resistivity was low and the heat dissipation properties were excellent.

[0193] On the other hand, as shown in Table 3, in Comparative Example 1 and Comparative Example 5, the first porosity was less than 15%, and it was found that the heat dissipation properties were poor.

[0194] In Comparative Example 2, it was found that the first porosity was more than 50% and the volume resistivity was high.

[0195] In Comparative Example 3, Comparative Example 4, and Comparative Example 6, the second porosity was the same as the first porosity or was larger than the first porosity, and it was found that the volume resistivity was high.

[0196] [Examples 17 and 18] In each of Examples 17 and 18, a conductive laminate was obtained in the same manner as in Example 1, except that the firing temperature in the firing step was changed.

[0197] The conductive laminates obtained in Examples 17 and 18 were used to measure the first porosity and the second porosity, and evaluations were performed on the volume resistivity, heat dissipation, and deformation of the substrate. In addition, the conductive laminate obtained in Example 1 was used to evaluate the deformation of the substrate. The evaluation methods for the volume resistivity and heat dissipation were the same as the above evaluation methods. The evaluation method for the deformation of the substrate was as follows.

[0198] <Deformation of the substrate> The substrate was placed on a desk and the degree of lifting was measured to evaluate the deformation of the substrate. The evaluation criteria are as follows: Rank 2 or higher is a level that is not problematic in practical use. 3: The floating from the base material is less than 2 mm. 2: The floating from the base material is 2 mm or more and less than 5 mm. 1: The floating from the base material is 5 mm or more.

[0199] [Table 4]

[0200] As shown in Table 4, in Example 1, the baking temperature in the step of baking the first conductive ink was 250°C or less, and the baking time was 1 to 120 minutes, and it was found that the volume resistivity was lower and the substrate deformation was smaller than in Example 17.

[0201] In Example 1, the baking temperature in the step of baking the second conductive ink was 250°C or lower, and the baking time was 1 to 120 minutes, and it was found that compared to Example 18, this resulted in excellent heat dissipation and small deformation of the substrate.

[0202] [Example 19] In Example 19, a conductive laminate was obtained in the same manner as in Example 2, except that the time from the end of the first application step to the start of the first baking step was changed to 60 seconds. In the conductive laminate of Example 19, the thickness of the conductive ink film was 7 μm.

[0203] The conductive laminate obtained in Example 19 was used to measure the first porosity and the second porosity, and the volume resistivity, heat dissipation, and resolution were evaluated. The conductive laminate obtained in Example 2 was used to evaluate the resolution. The evaluation methods for the volume resistivity and heat dissipation were the same as the above evaluation methods. The evaluation method for the resolution was as follows.

[0204] <Resolution> In each of Example 2 and Example 19, five conductive laminates were prepared. The width of each conductive laminate was measured and the average value was calculated. The length of each conductive laminate was measured and the average value was calculated. The width and length were measured using a ruler and a digital microscope (Dino-Lite Premier2 S Polarizer). The total deviation from 5 cm in width and 10 cm in length was taken as the dimensional difference. The resolution was evaluated based on the dimensional difference. The evaluation criteria are as follows. Rank 2 or higher is a level that does not pose a problem in practical use. Dimension difference = |Average width - 5cm| + |Average length - 10cm| 3: The dimensional difference is 1 mm or less. 2: The dimensional difference is more than 1 mm and less than 1.5 mm. 1: The dimensional difference is more than 1.5 mm.

[0205] [Table 5]

[0206] As shown in Table 5, in Example 2, the time from the end of the first application step to the start of the first firing step was 1 second, and it was found that the second porosity was lower, the volume resistivity was lower, and the resolution was superior compared to Example 19, in which the time was 60 seconds.

[0207] The disclosure of Japanese Patent Application No. 2020-165596, filed on September 30, 2020, is incorporated herein by reference in its entirety. In addition, all documents, patent applications, and technical standards described herein are incorporated herein by reference to the same extent as if each individual document, patent application, and technical standard was specifically and individually indicated to be incorporated by reference.

Claims

1. A substrate and a conductive ink film provided on the substrate, the conductive ink film is an ink film formed by baking an ink containing a metal salt or a metal complex; In the conductive ink film, when a surface closer to the substrate is defined as a first main surface and a surface farther from the substrate is defined as a second main surface, A first porosity in a region from a 50% thickness position from the first main surface toward the second main surface to the second main surface is 15% to 50%, and A second porosity in a region from the first main surface to a 10% thickness position toward the second main surface is smaller than the first porosity; The first porosity is 30% to 40%. Conductive laminate.

2. The conductive laminate according to claim 1 , wherein the second porosity is 20% or less.

3. 3. The conductive laminate according to claim 1, wherein the conductive ink film contains at least one metal selected from the group consisting of silver, gold, platinum, nickel, palladium, and copper.

4. The conductive laminate according to any one of claims 1 to 3, wherein the conductive ink film has a thickness of 0.5 µm to 30 µm.

5. applying a first conductive ink containing a metal salt or a metal complex onto a substrate; baking the first conductive ink; applying a second conductive ink containing metal particles onto the baked first conductive ink; and baking the second conductive ink, The conductive laminate is A substrate and a conductive ink film provided on the substrate, the conductive ink film is an ink film formed by baking an ink containing a metal salt or a metal complex; In the conductive ink film, when a surface closer to the substrate is defined as a first main surface and a surface farther from the substrate is defined as a second main surface, A first porosity in a region from a 50% thickness position from the first main surface toward the second main surface to the second main surface is 15% to 50%, and A method for manufacturing a conductive laminate, wherein a second porosity in a region from the first main surface to a 10% thickness position toward the second main surface is smaller than the first porosity.

6. The method for producing a conductive laminate according to claim 5 , wherein the metal particles are particles containing at least one type selected from the group consisting of silver, gold, platinum, nickel, palladium, and copper.

7. 7. The method for producing a conductive laminate according to claim 5, wherein the metal particles have an average particle size of 10 nm to 200 nm.

8. The method for producing a conductive laminate according to any one of claims 5 to 7, wherein the content of the metal particles is 10% by mass to 90% by mass with respect to the total amount of the first conductive ink.

9. The method for producing a conductive laminate according to any one of claims 5 to 8, wherein the metal salt and the metal complex each contain at least one selected from the group consisting of silver, gold, platinum, nickel, palladium, and copper.

10. the metal complex is a metal complex having a structure derived from at least one selected from the group consisting of an ammonium carbamate-based compound, an ammonium carbonate-based compound, an alkylamine, and a carboxylic acid having 8 to 20 carbon atoms; The method for producing a conductive laminate according to any one of claims 5 to 9, wherein the metal salt is a metal carboxylate having 8 to 20 carbon atoms.

11. The method for producing a conductive laminate according to any one of claims 5 to 10, wherein the content of the metal salt and the content of the metal complex are each 10% by mass to 90% by mass with respect to the total amount of the second conductive ink.

12. In the step of applying the first conductive ink, the first conductive ink is applied using an inkjet recording method; The method for producing a conductive laminate according to any one of claims 5 to 11, wherein in the step of applying the second conductive ink, the second conductive ink is applied using an inkjet recording method.

13. The method for manufacturing a conductive laminate according to any one of claims 5 to 12, wherein in the step of applying the first conductive ink, a temperature of the substrate when applying the first conductive ink is 20°C to 120°C.

14. The method for producing a conductive laminate according to any one of claims 5 to 13, wherein in the step of baking the first conductive ink, the baking temperature is 250°C or less and the baking time is 1 minute to 120 minutes.

15. The method for manufacturing a conductive laminate according to any one of claims 5 to 14, wherein in the step of applying the second conductive ink, a temperature of the substrate when applying the second conductive ink is 20°C to 120°C.

16. The method for producing a conductive laminate according to any one of claims 5 to 15, wherein in the step of baking the second conductive ink, the baking temperature is 250°C or less and the baking time is 1 minute to 120 minutes.

17. The method for manufacturing a conductive laminate described in any one of claims 5 to 16, wherein the time from the end of the process of applying the first conductive ink to the start of the process of baking the first conductive ink is 60 seconds or less.

Citation Information

Patent Citations

  • Conductive substrate

    JP2010192841A

  • Connection structure and manufacturing method of the same

    JP2016033941A

  • Sintering composition, method for producing silver nanoparticle, circuit board, and method for producing circuit board

    JP2020009633A